(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Magic realism or magical realism is an aesthetic style orgenre of fiction in which magical elements blend with the real world.Midnight’s child deals with life, exuberance and fantasy. ‘Salman- Rushdie’ isa narrative conjuror of genuine skill. As per various critics, Midnight’schildren is said to be picaresque novel, “a Bildungsroman in the negativesense”, “a very modernistic mixture of naturalistic background and surrealisticforeground”, and eminently political novel between myth, irony, magic and the flairof an oriental fairy tale. The ingredients of the European novel can be tracedin the novel such as realism, psychology interwoven into the pattern of magicalgenre. Magical realism can be seen as a device biding Indian culture of thepast to the contemporary multicultural interface. Rushdie’s principal use ofmagical realism in the text involves the telepathic abilities of saleem andother thousand and one children born at the stroke of midnight on August 15,1947, abilities that enable them to communicate them with each other and insaleem’s case to read the mind of those around him.